ANALISIS MAȘLAHȂT TERHADAP PRAKTIK PENETAPAN HARGA ECERAN TERTINGGI LPG 3 KG DI PANCA LAUTANG KAB. SIDRAP - Nurhasnah Hasyim; Fikri; Rusdaya Basri; Aris (DIKTUM: Jurnal Syariah dan Hukum, 2020)
This paper examines the maslahah analysis of practice of determination of the highest price of 3 kg LPG in Panca Lautang, Sidenreng Rappang Regency, consisting of three problems, namely; 1) what is the practice of determination of the highest price of 3 kg LPG in Panca Lautang, Sidenreng Rappang Regency?; 2) how is the effectiveness of Perda No. 12 of 2014 concerning LPG 3 kg in Panca Lautang, Sidenreng Rappang Regency ?; 3) how is the implementation of maslahah values in the practice of setting the highest retail prices of 3 kg LPG in Panca Lautang, Sidenreng Rappang Regency?.This paper uses qualitative research methods. The focus of the study is the determination of the highest price of 3 kg LPG. Location of study in Panca Lautang, Sidenreng Rappang Regency.The results of this study indicate that1) The practice of the determination of the highest price of 3 kg LPG in Panca Lautang, Sidenreng Rappang Regency, was found that Pangkalan still ignored regional regulations, due to several reasons such as transportation costs, capital, and the uncontrolled distribution chain; 2) Effectiveness of Perda No. 12 of 2014 concerning LPG 3 kg in Panca Lautang, Sidenreng Rappang Regency to implement retail prices is considered ineffective even though the Government intends to protect the public from arbitrary prices, and provide guarantees of justice; 3) The implementation of maslahah values in the practice of setting the highest retail price of 3 kg LPG in Panca Lautang, Sidenreng Rappang Regency is legal protection for consumers in setting the highest retail price, fighting for consumers or the poor to get their rights.